A Dynamic Model of Contractual Choice in Tenancy - Ananish Chaudhuri (Rutgers University, Department of Economics, 1997)
Two issues in land tenure contracts in agriculture that have vexed economists are (1) the appearance and co-existence of multiple contracts, often in adjoining plots of land and (2) the choice of a share-cropping contract because a share contract being analogous to a proportional tax, is supposed to distort incentives and lead to sub-optimal use of inputs into land as well as lower levels of investment. In this paper we develop a dynamic two period model of landlord-tenant interaction in a principal-agent framework with one sided private information. The landlord has a choice of three contracts - wage, share and rent and chooses a contract so as to maximize her own pay-off. We show that under certain realistic assumptions (1) multiple contracts can co-exist over time and (2) share-cropping can arise and persist. The driving force in the model is the rate at which the agent discounts the future.
Keywords: D82; L14; O12; 330; Adverse selection; Discount rate; Principal-agent model; Share-cropping; Tenurial contracts